Enhancing the Antifungal Efficacy of Fluconazole with a Diterpene: Abietic Acid as a Promising Adjuvant to Combat Antifungal Resistance in Candida spp. - Maria Gabriely de Lima Silva; Luciene Ferreira de Lima; Victor Juno Alencar Fonseca; Lucas Yure Santos da Silva; Ana Cecília Calixto Donelardy; Ray Silva de Almeida; Cícera Datiane de Morais Oliveira-Tintino; Anita Oliveira Brito Pereira Bezerra Martins; Jaime Ribeiro-Filho; Maria Flaviana Bezerra Morais-Braga; Saulo Relison Tintino; Irwin Rose Alencar de Menezes (MDPI AG, 2023)
The increasing antifungal resistance rates against conventional drugs reveal the urgent need to search for new therapeutic alternatives. In this context, natural bioactive compounds have a critical role in antifungal drug development. Since evidence demonstrates that abietic acid, a diterpene found in Pinus species, has significant antimicrobial properties, this study aimed to evaluate the antifungal activity of abietic acid against Candida spp and its ability to potentiate the activity of fluconazole. Abietic acid was tested both individually and in combination with fluconazole against Candida albicans (CA INCQS 40006), Candida krusei (CK INCQS 40095), and Candida tropicalis (CT INCQS 40042). The microdilution method was used to determine the IC50 and the cell viability curve. Minimum Fungicidal Concentration (MFC) was determined by subculture in a solid medium. The plasma membrane permeability was measured using a fluorescent SYTOX Green probe. While the IC50 of the drugs alone ranged between 1065 and 3255 μg/mL, the IC50 resulting from the combination of abietic acid and fluconazole ranged between 7563 and 160.1 μg/mL. Whether used in combination with fluconazole or isolated, abietic acid exhibited Minimum Fungicidal Concentration (MFC) values exceeding 1024 μg/mL against Candida albicans, Candida krusei and Candida tropicalis. However, it was observed that the antifungal effect of fluconazole was enhanced when used in combination with abietic acid against Candida albicans and Candida tropicalis. These findings suggest that while abietic acid alone has limited inherent antifungal activity, it can enhance the effectiveness of fluconazole, thereby reducing antifungal resistance.